Status of soil cover on the degree ofaccumulation of heavy metals in the soil of the industrial region (Karaganda city) - Mukasheva, M.A.; Nugumanova, Sh.M. (Fundamental and Experimental Biology, 2017)
In article the condition of a soil cover of the city of Karaganda is studied. To this end, there have been ranked according to the highest degree of pollution. It was revealed that the dynamics of hygienic indices for 3 years is unfavorable with respect to the soil in the residential area. Against the background of the general tendency to reduce the level of soil pollution in the zone of influence of enterprises, the soil in the industrial area of the city is heavily polluted. The most intensive soils are contaminated with substancesbelonging to the first and second hazard classes: lead, zinc, copper and nickel. The content of zinc exceeds the MPC by approximately 3 times, lead by 1.5 times, copper by 1.6 times, nickel by 1.3 times. Such differences in the formation of zones of high and low soil polluted cities, to some extent, may be associated withage, the industrial development of the city, which was formed in the past 50–60 years, and much younger.